2015
DOI: 10.1111/pai.12346
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus‐induced airway cytokines and respiratory morbidity in severely premature children

Abstract: Background Rhinovirus (RV) has been linked to the pathogenesis of asthma. Prematurity is a risk factor for severe RV infection in early life, but is unknown if RV elicits enhanced pro-asthmatic airway cytokine responses in premature infants. This study investigated if young children born severely premature (<32 weeks gestation) exhibit airway secretion of Th2 and Th17 cytokines during natural RV infections and if RV-induced Th2-Th17 responses are linked to more respiratory morbidity in premature children durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 22 publications
(44 reference statements)
1
55
0
Order By: Relevance
“…[41,42] The concentrations of nasal TSLP in our naturally acquired infections series, were significantly higher, not only in RSV and rhinovirus infections, but also in PIV and adenovirus-infants with bronchiolitis. The highest levels of TSLP were identified, in our patients, in infants with RSV + HRV coinfections.…”
Section: Discussionmentioning
confidence: 91%
“…[41,42] The concentrations of nasal TSLP in our naturally acquired infections series, were significantly higher, not only in RSV and rhinovirus infections, but also in PIV and adenovirus-infants with bronchiolitis. The highest levels of TSLP were identified, in our patients, in infants with RSV + HRV coinfections.…”
Section: Discussionmentioning
confidence: 91%
“…Prior studies suggest this may be due to airway immune cytokine dysregulation. In a study by Perez et al, it was observed that premature children have dysregulated T helper (Th) 2 and Th17 airway cytokine immune responses to RV infection, which might be a potential reason for increased sensitivity to RV in premature children during early life [13]. Furthermore, systemic innate immune responses [14,15] and antibody-mediated immunity [16], which depends on maternal transfer of specific IgG across the placenta, seem to be dysregulated in premature babies [14,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Demographic variables comprised of gestational age (GA) in weeks, age, gender, and ethnicity. For the purpose of the study, clinical parameters were characterized as binary outcomes for the presence of wheezing, and the classification of severe prematurity defined a priori by a GA of less than 32 weeks, to include extremely preterm and very preterm subjects, based on the World Health Organization (WHO) definition of prematurity [12,13]. …”
Section: Methodsmentioning
confidence: 99%
“…Although damage to the developing airways and altered immune responses are thought to be the main mechanisms through which RV could induce asthma and airway hyperreactivity later in life [107,108], others have suggested that early-life infection with RV might be the first indication of the pre-existing tendency in some children to develop asthma, including among preterm infants [109,110]. The ability of RV to induce prolonged and exaggerated inflammatory responses after the initial infection has been described as a potential contributor to the development of chronic respiratory morbidity among preterm infants, with limited data demonstrating increased airway secretion of inflammatory cytokines and remodelling molecules during acute RV infection, particularly among those with BPD [108,111]. The dysregulated immune response to RV infection was associated longitudinally with more severe respiratory morbidity, increased hospitalisation and requirement for intensive care admission during the first 2 years of life [108].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…The ability of RV to induce prolonged and exaggerated inflammatory responses after the initial infection has been described as a potential contributor to the development of chronic respiratory morbidity among preterm infants, with limited data demonstrating increased airway secretion of inflammatory cytokines and remodelling molecules during acute RV infection, particularly among those with BPD [108,111]. The dysregulated immune response to RV infection was associated longitudinally with more severe respiratory morbidity, increased hospitalisation and requirement for intensive care admission during the first 2 years of life [108]. …”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%